728Comparative performance of WHO-5, PHQ-9 and PSS Scale for screening antenatal depression and suicide risk. (2nd September 2021) - Do, Phuc Huyen; Vo, Van Thang; Luong-Thanh, Bao-Yen; Nguyen, Lan Hoang; Valdebenito, Sara; Eisner, Manuel; Tran, Xuan Bach; Baker, Philip; Dunne, Michael
Abstract: Background: This study evaluated the psychometric properties of three self‐reported scales including WHO Well-Being Index (WHO-5), Patient Health Questionnaire-9 items (PHQ-9), and Perceived Stress Scale (PSS) for determining the severity of antenatal depression and suicide risk. Methods: Extracted from a multi-site birth cohort study in eight countries, we test the reliability and validity of tri-scales among 148 women in the third trimester and 3-months after childbirth in Vietnam. Results: Reliability testing achieved good internal consistency for the set of scales (Alpha = 0.75–0.81). The multitrait‐multimethods matrix and SEM model indicated a good fit [Chi‐square (230) = 337.5, p < 0.001; Root Mean Square Error of approximation= 0.56, Comparative Fit Index= 0.91] and good discriminant validity of WHO-5 lower discriminant validity of PSS and PHQ-9. The proportion of correctly classified cases and optimum balanced indicators of sensitivity and specificity suggested the cut-off scores of ≥ 6 for PHQ-9 and ≥ 25 for PSS for suicide risk screening. Regarding to predictive validity for postpartum depression of PHQ-9, we found that the cut-off scores of ≥ 6 for prenatal PHQ-9 screening can predict approx.70% of mild postpartum depression cases after 3-month childbirth. Conclusions: This present study suggested adequate validity and reliability of the WHO-5, PHQ9 and PSS to measure antenatal depression and suicide risk in Vietnam. Key messages: Further studies might consider to use one or a set of scales to understand multiple domains of mental disorder as it is simple to administer and acceptable duration for completion in the community.